The Application of Lean Manufacturing for Operation Improvement: A Case Study of Black Cough Medicine Production in Indonesia - Pramadona, Pramadona; Adhiutama, Akbar (School of Business and Management Institut Teknologi Bandung, 2013)
Nowadays, the pharmaceutical industry has a market tends to be unstable and volatile in meeting customer needs. This is due to the economic crisis that occurred in different parts of the world. The pharmaceutical industry currently uses good manufacturing practices (cGMP) to ensure that products are consistently produced and controlled according to the required standards. Pharmaceutical industry slowly started to move from cGMP to lean manufacturing that focused on reducing operating costs while ensuring compliance. The purpose of this paper is to analyze the usage of lean manufacturing instead of the usage of cGMP to eliminate wastes. To conduct this study, literature review and company visit has been done. This analysis was applied by using value stream mapping (VSM) and 7-wastes methodology to analyze the problems in the OBH (Black Cough Medicine) production line one of the pharmaceutical industry in Bandung, Indonesia. For the improvement, the lean manufacturing approach has been carried out and the future VSM has been developed. Finding reveals that the application of lean manufacturing in the cGMP environment helps the company to eliminate wastes in reducing lead time and cycle time in the manufacturing process.Ã‚Â Keywords: pharmaceutical industry, cGMP, lean manufacturing, value stream mapping, 7-wastes.